2004
DOI: 10.1126/science.1095109
|View full text |Cite
|
Sign up to set email alerts
|

Side-On Copper-Nitrosyl Coordination by Nitrite Reductase

Abstract: A copper-nitrosyl intermediate forms during the catalytic cycle of nitrite reductase, the enzyme that mediates the committed step in bacterial denitrification. The crystal structure of a type 2 copper-nitrosyl complex of nitrite reductase reveals an unprecedented side-on binding mode in which the nitrogen and oxygen atoms are nearly equidistant from the copper cofactor. Comparison of this structure with a refined nitrite-bound crystal structure explains how coordination can change between copper-oxygen and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
309
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(341 citation statements)
references
References 39 publications
30
309
1
1
Order By: Relevance
“…Surprisingly, in our first structure (1.55-Å resolution; data not shown) of the ''as-isolated'' AcNiR we found that the T2Cu site had NO bound in a side-on manner, similar to that reported recently for crystals of reduced Alcaligenes faecalis NiR exposed to NO under anaerobic conditions (20). Because we had not added exogenous NO, and because the crystals or protein had not been reduced, we decided to look at further crystals from the same bulk culture.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Surprisingly, in our first structure (1.55-Å resolution; data not shown) of the ''as-isolated'' AcNiR we found that the T2Cu site had NO bound in a side-on manner, similar to that reported recently for crystals of reduced Alcaligenes faecalis NiR exposed to NO under anaerobic conditions (20). Because we had not added exogenous NO, and because the crystals or protein had not been reduced, we decided to look at further crystals from the same bulk culture.…”
Section: Resultssupporting
confidence: 55%
“…These studies have been in general agreement that nitrite binds to the T2Cu ion via O in an asymmetric bidentate fashion. Recently, Tocheva et al (20) have noted a face-on interaction of the nitrite with Cu in their most recent 1.4-Å resolution structure compared with previous observations of bent O coordination. An examination of the Protein Data Bank (21) reveals a significant variation in the position and orientation of nitrite in the nitrite-bound CuNiRs.…”
mentioning
confidence: 99%
“…For example, a membrane-associated nitrite reductase metabolon with deoxyHb and metHb, anion exchange protein, carbonic anhydrase, aquaporin, and rhesus channels could bring together nitrite, proton, deoxyheme, and highly hydrophobic channels that could serve to concentrate the lipophilic NO at the membrane complex (52). Indeed, the heme pocket distal histidine may donate a proton to the reaction, an effect analogous to the proton donation by aspartate in the bacterial nitrite reductase enzyme (53). This histidine proton donation to nitrite would serve to both position and stabilize nitrite in the heme pocket and accelerate the reaction by forming nitrous acid.…”
Section: Discussionmentioning
confidence: 99%
“…The atomic coordinates and structure factors (code 2DWS,2DY2,and 2DWT) have been argued that it is actually the protonated HNO 2 species that binds to the active site (16,17). Recent studies have shown that before the NO (g) product leaves the type 2 copper site, it is bound to the copper ion as a side-on copper-nitrosyl intermediate (17,18). Near the type 2 site there are also the catalytic residues Asp-129 and His-287, which have been found to be crucial to enzyme activity and nitrite binding (9, 16, 19 -22).…”
mentioning
confidence: 99%